Meta-analisis : Pengaruh Penerapan Gamifikasi dalam Pembelajaran Berbantu Aplikasi Quizizz Terhadap Hasil Belajar Biologi Siswa SMA - Andi Rahmat Saleh; Sitti Saenab; Andi Tenri Ampa Nurfitria Papada (Celebes Science Education, 2023)
The rapid technological developments globally have brought big changes to The Times. In the educational world application of technology is desperately needed and will contribute space for students to be able to explore potential and innovation as an implementation of the learning, which is consistent with the requirement in the 21st century of education that requires students to be able to grow knowledge and skills in an aspect of life. Therefore, it will take a great deal of fun to cultivate an interest and motivation in learning, which can be achieved with the help of varying media use or methods in learning. One of the tools deemed capable of realizing that is, with the application-aided gamizizz approach. Research with the title of the effectiveness of the application of the gamizizz application to the quizizz application to the increased high school student biology results was conducted with the purpose of knowing how much the gamizizz application may have affected the quizizz application of high school biology. The study is conducted with the application of the meta method - analysis using 7 articles from the journal of Indonesia as the subject of research. Based on research, it was found that application of gamizizz's AIDS to learning gives positive reinforfication when applied to high school x levels, in view.